Mineral phosphate solubilization activity of gluconacetobacter diazotrophicus under P-limitation and plant root environment - Crespo, Juan Manuel (2011)
The ability to solubilize insoluble inorganic phosphate compounds by Gluconacetobacter diazotrophicus was studied using different culture approaches. Qualitative plate assays using tricalcium phosphate as the sole P-source showed that G. diazotrophicus produced solubilization only when aldoses were used as the C-source. Extracellular aldose oxidation via a pyrroloquinoline quinone-linked glucose dehydrogenase (PQQ-GDH) is the main pathway for glucose metabolism in G. diazotrophicus. In batch cultures with 5 g l-1 of hydroxyapatite as the P-source and glucose as the C-source, more than 98% of insoluble P was solubilized. No solubilization was observed neither using glycerol nor culturing a PQQ-GDH mutant of G. diazotrophicus. Solubilizaton was not affected by adding 100 mmol l-1 of MES buffer. Continuous cultures of G. diazotrophicus showed significant activities of PQQ-GDH either under C or P limitation. An intense acidification in the root environment of tomato and wheat seedlings inoculated with a G. diazotrophicus PAL5 was observed. Seedlings inoculated with a PQQ-GDH mutant strain of G. diazotrophicus showed no acidification. Our results suggest that G. diazotrophicus is an excellent candidate to be used as biofertilizer because in addition to the already described plant growth-promoting abilities of this organism, it shows a significant mineral phosphate solubilization capacity.